RADICALISM IN INDONESIA: AN OVERVIEW OF THE INDONESIAN-BASED ISLAMIC MODERATION - Mhd. Rasidin; Imaro Sidqi; Doli Witro (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2021)
Islam, as a perfect religion, is a religion that brings grace to the universe (rahmatan lil alamin). However, in this modern era, Indonesian Muslims face significant challenges due to the emergence of reformist movement groups with extreme views, namely fundamentalism and radicalism. This is shown by the facts about the bombing carried out by a group of terrorists in the name of Islam. This gets a balance by Islam in this country, which is an Islam that holds a moderate principle, does not lean to the right or the left, but takes the middle path so as not to clash with one another. This principle is the strength of Islam in counteracting radicalism in Indonesia. The principle that does not incline towards an extreme right or an extreme to the left understanding of Islam but remains in the middle is identified with Islamic moderation. This article aims to describe the relevance of Islamic moderation in minimizing the spread of radicalism in Indonesia. This article is qualitative literature research. This study uses written materials in books, scientific articles, research reports, and articles published on news websites. The data analysis technique used was data reduction, data presentation, and conclusion drawing. The results of the analysis show that the Indonesian-based reconstruction of Islamic moderation, which has new distinctions or characteristics, is conceptually and practically crucial in reducing religious radicalism in Indonesia.